2016
DOI: 10.1021/acs.est.5b06326
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis between Low- and High-Cadmium-Accumulating Genotypes of Pakchoi (Brassica chinensis L.) in Response to Cadmium Stress

Abstract: To reduce cadmium (Cd) pollution of food chains, screening and breeding of low-Cd-accumulating cultivars are the focus of much study. Two previously identified genotypes, a low-Cd-accumulating genotype (LAJK) and a high-Cd-accumulating genotype (HAJS) of pakchoi (Brassica chinesis L.), were stressed by Cd (12.5 μM) for 0 h (T0), 3 h (T3) and 24 h (T24). By comparative transcriptome analysis for root tissue, 3005 and 4343 differentially expressed genes (DEGs) were identified in LAJK at T3 (vs T0) and T24 (vs T3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
97
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(115 citation statements)
references
References 78 publications
15
97
1
Order By: Relevance
“…In current study, some DEGs associated with microtubule-based process were exclusively up-regulated during an earlier stage (T7) in B2013, yet similar transcriptional changes did not observed in 90196 at the same stage, indicating that the microtubule may participated directly in host defense response to P. brassicae in resistant genotype. Besides, the genes that were involved in DNA repair participated in an early response to P. brassicae , due to detecting many up-regulated helicase-encoding genes both in B2013 and 90196 at T7, corroborating the findings of Zhou et al (2016) regarding the response to Cd accumulation in Brassica chinensis .…”
Section: Discussionsupporting
confidence: 71%
“…In current study, some DEGs associated with microtubule-based process were exclusively up-regulated during an earlier stage (T7) in B2013, yet similar transcriptional changes did not observed in 90196 at the same stage, indicating that the microtubule may participated directly in host defense response to P. brassicae in resistant genotype. Besides, the genes that were involved in DNA repair participated in an early response to P. brassicae , due to detecting many up-regulated helicase-encoding genes both in B2013 and 90196 at T7, corroborating the findings of Zhou et al (2016) regarding the response to Cd accumulation in Brassica chinensis .…”
Section: Discussionsupporting
confidence: 71%
“…In this work, many DEGs and DEPs were identified between the two types of pineapple, namely, CP and SC, which are categorized as Queen and Cayenne, respectively, before the ethephon induction treatment, which suggested that there are basic differences between CP and SC. Similar results occurred in the reports of the seasonal and continuous flowering roses in response to floral transition [34] as well as for low-and high-cadmium-accumulating genotypes of pakchoi (Brassica chinensis L.) in response to cadmium stress [35]. In particular, the results revealed that the expression levels of the ETR and ERF genes were lower in CP than in SC before the ethephon induction treatment, whereas those of the ACS and ACO genes were higher.…”
Section: Variation In the Basic Ability Of Ethylene Signal Transductisupporting
confidence: 87%
“…High and low Cd accumulation cultivars have been identified in many crops, such as rape (Niu, 2012; Wu et al, 2015), pakchoi (Zhou et al, 2016), watercress (Wang et al, 2015), and Chinese leaf mustard (Dai et al, 2012). Differences in Cd absorption and accumulation among different turnip cultivars or genotypes also have been indicated in studies around the world (Bingham et al, 1975; Molahoseini and Feizi, 2012; Parveen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cruciferous plants are generally considered to represent the largest proportion of HM hyperaccumulators (He et al, 2009), and the earliest identified and most reported Cd hyperaccumulators are members of the Brassicaceae family (Zhao et al, 2002). In recent years, many studies of Cd absorption and accumulation have been performed for common cruciferous crops, such as rape (Carrier et al, 2003; Wang et al, 2009), Chinese cabbage (Aziz et al, 2015; Wu et al, 2015), pakchoi (Chen et al, 2010; Zhou et al, 2016), broccoli (Pedrero et al, 2008), and radish (Lagerwer, 1971; Vitoria et al, 2003; Lin et al, 2014). These studies provide useful information on food safety and potential of soil remediation of these plants.…”
Section: Introductionmentioning
confidence: 99%